A Survey on Business Profitability by Digital Marketing Strategies of Facebook - JAIN, DR MANJULA (The journal of contemporary issues in business and government, 2021)
Digital marketing is the way of marketing followed by new age marketers. In modern times traditional practices of marketing appear to be less effective in terms of giving output. With the advancement of technology new age marketers are moving towards digital marketing. Digital marketing has become a new way of marketing and reaching directly to the target audience without putting much time, but a clear statistic data related to effectiveness of digital media marketing especially Facebook is not known. The current survey puts light on the effectiveness of digital media marketing – Facebook in advertisement of products and increased sales of articles. The survey conducted shows that Social media platform – Facebook as a potential medium of carrying out promotional activities and results in increased sales of a product. Thus current study opens the future perspective to conduct more research on the connection of different social media platform and shopped articles.